What is the Transformational Learning Experience of Secondary Teachers Who Have Dealt with Burnout? - Dr. Julius R. Sims (Adult Education Research Conference, 2015)
Burnout is a syndrome consisting of emotional exhaustion (EE) and depersonalization (DPZ) (Yong & Yue, 2007). Educators who fall victims to burnout are likely to be less sympathetic toward learners, have a lower tolerance for disruptions within the learning process, be less apt to prepare adequately for content delivery and student interaction, and feel less committed and dedicated to their work (Fisher, 2011). A phenomenological study explored the burnout experiences among eight secondary teachers and their strategies for coping. Using in-depth interviews, the researcher was able to understand the personal meanings, expressed opinions, feelings, and other detailed descriptions of the participants' burnout experiences. Administration issues, administrative workload, negative teacher/student relationships, and lack of student effort were resulting themes associated with EE and DPZ effecting teaching performance. In contrast, mental efficiencies, interpersonal relationships, and outside resources were themes associated with the coping activities/strategies of participants. Consequently, learning and employing affective strategies that cope with burnout can help educators become more effective in their professional field (Maslach, 2003; Zonlnierczyk-Zreda, 2005). This study seeks to add to the adult education research in further understanding the transformational learning process of adults; and the social or environmental context that influences the learning that adults encounter.